Executive Neutrality and Partisan Politics in Indonesia’s Presidential System: Reassessing the Constitutional Boundaries of Presidential Power - Rahayu Fitri , Rizki; Ayu Eviani Yuliantari , I Gusti; Amir , Irfan; Aris , Ismail; Jaedin (IAIN Bone, 2025)
This study examines presidential neutrality in Indonesia’s presidential system, emphasizing its importance in safeguarding democratic fairness and electoral integrity. Using a normative legal approach, the research analyzes constitutional provisions, legislation, and state practices to assess how the President’s dependence on political parties generates conflicts of interest that undermine executive impartiality. The findings reveal that, despite legal prohibitions on partisan involvement by state officials, weak enforcement and the absence of an independent supervisory body perpetuate the erosion of neutrality within the executive branch. This gap between constitutional ideals and political practice highlights the vulnerability of Indonesia’s democracy to partisan influence. The study recommends reformulating the legal framework on executive neutrality, establishing an independent oversight institution, and promoting merit-based cabinet appointments to strengthen democratic integrity and the quality of governance.